The quest for mental health a tale of science, medicine, scandal, sorrow, and mass society - Dowbiggin, Ian Robert, 1952- (Cambridge essential histories., 2011)
"This is the story of one of the most far-reaching human endeavors in history: the quest for mental well-being. From its origins in the eighteenth century to its wide scope in the early twenty-first, this search for emotional health and welfare has cost billions. In the name of mental health, millions around the world have been tranquilized, institutionalized, psycho-analyzed, sterilized, lobotomized and even euthanized. Yet at the dawn of the new millennium, reported rates of depression and anxiety are unprecedentedly high. Drawing on years of field research, Ian Dowbiggin argues that if the quest for emotional well-being has reached a crisis point in the twenty-first century, it is because mass society is enveloped by cultures of therapism and consumerism, which increasingly advocate bureaucratic and managerial approaches to health and welfare"--